PUBLIC SCHOOL EFFICIENCY USING DATA ENVELOPMENT ANALYSIS: AN EMPIRICAL APPLICATION FOR BRAZIL - Isabel Raposo; Tatiane Menezes (European Regional Science Association (ERSA), 2011)
This paper studies the educational efficiency as determined only by the variables directly controlled by the school, isolated from the influence of other environmental characteristics, such as student's socioeconomic status, that might influence efficiency as well. An alternative application of Simar and Wilson (2007) two-stage DEA's approach is adopted using data from public schools in the basic education level from the Northeast Region of Brazil. The results have showed that the rank of efficiency becomes much more homogeneous after isolating from the effect of environmental variables as compared to the rank produced from a simple one-stage DEA.
Keywords: 330